Consideration of ‘Urf in the Judgments of the Khulafa' al Rashidun and the Early Fuqaha (American Journal of Islam and Society, 1992)
Consideration of ‘Urf by the Khulafla’ al Rashidun‘Urf (custom) and ‘adah (tradition) are very ancient and importantsomes of Islamic law. As the pre-Islamic Arabs had no written documentsor script, their social systems were regulated by custom and tradition.According to the available historical accounts, the khulafa' alrashidun retained many pre-Islamic social customs and traditions and alsoadopted and established some useful nonindigenous customs. Such borrowingwas quite acceptable in their eyes, for the Prophet himself hadacknowledged the validity of some pre-Islamic customs that were compatiblewith the letter and spirit of the revelation.At the time of the Prophet, the Arabian peninsula was the home ofmany different customs and traditions. The Arabs were mainly idol worshippets,and this outlook was reflected in their customs. However, theyhad also retained a pottion of the legacy of Ibrahim: ceremonies relatedto the Ka‘bah and circumcision. These ceremonies provided the basis forthe establishment of social traditions.Many pre-Islamic customs were still practiced during the period ofthe khulafa’ al rashidun. For instance, grain (i.e., wheat, barley) continuedto be regarded as kayli (measured by capacity) and gold and silverwere considered wazni (me asured by weight). The same custom andusage were followed in commercial transactions made by the Prophet andhis four immediate successors. The fuqaha’ later based many of the rulesconcerning zakah (poor due), sadaqah (charity), and kaffarah (expiation) ...